Col sorriso sulle labbra. La satira tra libertà di espressione e dovere di rispetto (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazioneSOMMARIO 1. Introduzione - 2. La satira e il diritto alla libertà di espressione - 3. Satira, umorismo e rispetto - 4. Deridere la religione - 5. Le basi morali della libertà di satira - 6. Conclusioni.ABSTRACT: With a smile on the lips. The satire between freedom of expression and duty of respectThis paper argues for a liberal perspective about satire, rejecting the idea that satire should not have constraints, and trying to ground this perspective on a more articulate argument than the mere reference to the relevance of freedom of expression in Western societies.I will proceed in this way. In Section 2, I will clarify what satire is, and how it is connected to freedom of expression. Section 3 will be devoted to analyze the relationship between humour and respect, and to explain why satire is morally more problematic than liberals usually think. In Section 4 I will suggest that satire against religion can be sometimes considered a lack of respect for people who believe in that religion. In Section 5 I will argue against restricting satire, even if it is seriously disrespectful, producing two different arguments for two different situations: when the victim can be considered “a powerful person”, and when he/she can be considered “a disadvantaged person”.